Pengaruh Transfer Pricing dan Corporate Social Responsibility terhadap Agresivitas Pajak - Pesta Ria Pasaribu; Wiwit Irawati (Universitas Pamulang, 2022)
Tax revenues that have not been maximized are suspected to be part of the result of transfer pricing and corporate CSR activities. This study aims to determine the effect of transfer prices and corporate social responsibility on tax aggressiveness. This type of research is quantitative research. The data used in this research is secondary data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the energy sector and consumer non-cyclical in 2017-2020. The sampling technique used purposive sampling and obtained as many as 16 companies with a research period of 4 years so that 64 sample data were obtained. Analysis of the data used in this study is descriptive statistics, panel data regression test, classical assumption test and hypothesis testing. The results show that transfer pricing has no significant effect on tax aggressiveness, but corporate social responsibility has a significant effect on tax aggressiveness